In vitro bonding effectiveness of self-etch adhesives with different application techniques: A microleakage and scanning electron microscopic study - Nagpal, Rajni (Medknow Publications, 2011)
AIM: To evaluate and compare the microleakage of self-etch adhesives placed under different clinical techniques and to analyze the resin–dentin interfacial ultrastructure under scanning electron microscope (SEM). MATERIALS AND METHODS: 100 extracted human premolars were divided into two groups for different adhesives (Clearfil S(3) and Xeno III). Class V cavities were prepared. Each group was further divided into four subgroups (n = 10) according to the placement technique of the adhesive, i.e. according to manufacturer's directions (Group 1), with phosphoric acid etching of enamel margins (Group 2), with hydrophobic resin coat application (Group 3), with techniques of both groups 2 and 3 (Group 4). The cavities were restored with composite. Ten samples from each group were subjected to microleakage study. Five samples each of both the adhesives from groups 1 and 3 were used for SEM examination of the micromorphology of the resin–dentin interface. RESULTS: At enamel margins for both the adhesives tested, groups 2 and 4 showed significantly lesser leakage than groups 1 and 3. At dentin margins, groups 3 and 4 depicted significantly reduced leakage than groups 1 and 2 for Xeno III. SEM observation of the resin–dentin interfaces revealed generalized gap and poor resin tag formation in both the adhesives. Xeno III showed better interfacial adaptation when additional hydrophobic resin coat was applied. CONCLUSIONS: In enamel, prior phosphoric acid etching reduces microleakage of self-etch adhesives, while in dentin, hydrophobic resin coating over one-step self-etch adhesives decreases the microleakage.